The Internal and External Public Debt Structure in India: Trend and Sustainability Analysis - Dr.P.A. Naidu (Journal of Macroeconomics and Social Development, 2026)
Public debt plays a crucial role in fiscal management, macroeconomic stabilization and developmental financing in emerging economies. In India, increasing developmental commitments, infrastructure expenditure, fiscal deficits and economic stimulus measures have significantly influenced public debt accumulation over the years. The present study ex-amines the structure, trend and sustainability of internal and external public debt in India during the period 2000–01 to 2023–24. The study is based on annual secondary data collected from Reserve Bank of India (RBI), Ministry of Finance publications, Union Budget documents, Economic Survey reports and World Bank databases. The analysis focuses on internal debt, external debt, debt composition and debt growth patterns in India. Descriptive statistics, compound annual growth analysis, trend analysis and correlation techniques are employed to evaluate debt dynamics and sustainability patterns. The empirical findings indicate that internal debt constitutes the dominant share of total public debt in India throughout the study period. The growth of internal debt accelerated significantly after the global financial crisis and COVID-19 pandemic due to rising fiscal deficits and expansion-ary fiscal policies. External debt also increased steadily but remained relatively moderate compared to internal debt. The findings further reveal that increasing developmental expenditure and fiscal imbalances significantly contributed towards debt accumulation. The study concludes that efficient debt management, fiscal discipline and productive utilization of borrowed resources are essential for maintaining long-term debt sustainability and macroeconomic stability in India.